The Optimal Acoustic Measurement Point Selection for UHV Reactors in Substations Based on Equivalent Impedance and Information Entropy Theory - Yingwen Li; Zhen Wei; Huilian Liao; Lin Li; Peizhong Zhang; Jingyun Zhao (IEEE Access)
The operation of an Ultra-High Voltage (UHV) shunt reactor generates significant acoustic signals containing crucial information. To accurately assess the various acoustic parameters of ultra-high voltage shunt reactors, it is crucial to establish an accurate acoustic field model and find the optimal acoustic measurement point for their voiceprint monitoring. This article first collects the surface acoustic signals of the reactor oil tank to form the equivalent sound source of the reactor. Considering the influence of the firewall on the radiated sound field, the complex model of the firewall is simplified using equivalent transfer impedance as the boundary condition. The boundary element method is employed to establish the model, and the optimal acoustic measurement point position in space is obtained by calculating the information entropy of the sound source and external measurement points. Finally, the model accurately reconstructed and simulated the near-field of the parallel reactor, and achieved quantitative evaluation of the optimal voiceprint detection position. The results indicate the high accuracy and reliability of the sound field reconstruction model, significantly improving computational efficiency, and the measurement point can fully characterize the acoustic properties of the reactor. This study provides a reliable method for the deployment, comprehensive evaluation, and optimization of acoustic performance of ultra-high voltage parallel reactors for online monitoring of reactor voiceprint.